Just joking: jest as a defence to defamation - Thompson, Simon (Department of Private Law, 2024)
The South African law of defamation seeks to balance the plaintiff's right to reputation against the defendant's right to freedom of expression. Humour complicates this balance because its appreciation is hyper context-dependent and subjective, rendering the line between serious defamatory statements of fact and non-serious jokes difficult to draw. This dissertation discusses the ways in which the South African law of defamation regulates humorous statements, paying particular attention to the element of defamatoriness and the defences to an action for defamation. It argues that superiority humour, which is funny because it belittles the plaintiff, is being unduly curtailed by the courts' erroneous application of a flawed test for defamatoriness based on the plaintiff's mere exposure to ridicule. The undesirable result is that the defendant will be held liable for superiority humour even in those instances where the plaintiff has not been defamed. It also argues that humour should receive greater protection under the defences available to the defendant in an action for defamation, particularly the defence of qualified privilege.